Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1897)
Demorest's Family Magazine. July 1897. Vol. 33, No. 9. -- Queen Victoria -- Victorian Dresses -- The Last Six Months of Caroline Lenox -- We Two in Arcade -- Old Trinity and Its Tombs -- A Pen Portrait -- The First Flag-Maker of America -- An American Miniature-Painter: Amalia Kussner -- A Major-General in Petticoats -- Siberian Aborigines -- The College Woman and the Home -- Grant's Last Comrade -- Women as Journalists -- Society Fads -- Our Girls: Practical Hints to Young Women in Business -- The True Mother Instinct -- Home Art and Home Comfort: Novelties for Summer Furnishing -- Sanitarian: Practical Hints for Country Nursing -- Household: The Strawberry: In and Out of Season -- The World's Progress -- In the World of Letters and Art -- About Women -- Mirror of Fashions: Review of Fashions - July -- Correspondence Club -- Gleanings: The Diamond Jubilee -- Biographical Sketches for the Demorest's Magazine Portrait Album -- Spice Box
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print. Valdosta State University Archives and Special Collections. April 18, 2017.
Keywords: Illustrated Periodicals; Magazine; Children; Travel; Women's History; Fashion; Social History; Dressmaking; Needlework; Homemaking; 1800s; 19th Century